Optical biodetection of cadmium and lead ions in water - Haron, Saharudin; Ray, Asim K. (Elsevier BV, 2006)
A three layer waveguiding silicon dioxide (SiO2)/silicon nitride (Si3N4)/SiO2 structure on silicon substrate was proposed as an optically efficient biosensor for calibration of heavy metal ions in drinking water. The catalytic activities of urease and acetylcholine esterase (AchE) were inhibited by the presence of cadmium (Cd2+) and lead (Pb2+) ions. The detection limit as low as 1 ppb was achieved by employing the technique of total reflection at the interface between the Si3N4 core and composite polyelectrolyte self-assembled (PESA) membranes containing cyclotetrachromotropylene (CTCT) as an indicator.